131k views
0 votes
What is the expression for f(x) when we rewrite (1/32)^x times (1/2)^9x-5 as (1/2)^f(x)

User Mepler
by
5.0k points

1 Answer

3 votes

ANSWER


f(x) = 14x - 5

Step-by-step explanation

The given expression is


( (1)/(32))^(x) * ( (1)/(2))^(9x - 5) = ( (1)/(2) ) ^(f(x))

We rewrite the left hand side using the laws of indices.


( (1)/(2))^(5x) * ( (1)/(2))^(9x - 5) = ( (1)/(2) ) ^(f(x))

The bases are now the same on the LHS.

We write one base and add the exponents


( (1)/(2))^(5x + 9x - 5) = ( (1)/(2) ) ^(f(x))


( (1)/(2))^(14x- 5) = ( (1)/(2) ) ^(f(x))

Since the bases are equal, the exponents are also equal:


f(x) = 14x - 5

User Gabriel TN
by
5.1k points